HUBUNGAN PERILAKU SPIRITUAL DENGAN HASIL BELAJAR SISWA PADA PEMBELAJARAN SENI RUPA DI SMP N 1 ENOK INHIL RIAU - Arif Prasetyo, Zubaidah, Mediagus (Universitas Negeri Padang, 2013)
The purpose of this research to describe spiritual behavior and learning outcome of students at SMP N 1 Enok in Visual Art learning and to state was there relationship between both of variables. This research was descriptive correlational. Total sample of 86. Technique of data collection used questionnaire and value of Visual Art learning. Data analysis used Product Moment Pearson formula. Result of this research shown spiritual behavior 73,33%. Learning outcome was achieved sum of 76 with correlation coefficient 0,487** and Sig 0,00. Level of relationship was happened between both of variables that was moderate with direction of positive relationship.